Conditioned reinforcement and choice with delayed and uncertain primary reinforcers - Mazur, James E (Journal of the Experimental Analysis of Behavior, 1995)
In an adjusting-delay choice procedure, pigeons could peck on either a red key or a green key. A peck on the red key always led to a delay associated with red houselights and then food. The delay was adjusted over trials to estimate an indifference point-a delay at which the two keys were chosen about equally often. In some conditions, a peck on the green key led to food on all trials after delays of either 10 a or 30 s, and green houselights were lit during the delays. In other conditions, food was presented on only half of the green-key trials. If the green houselights continued to occur on both reinforcement and nonreinforcement trials, preference for the green key always decreased. Preference for the green key also decreased if half of the trials had 30-s houselights followed by food and the other half had no green houselights and no food. However, preference for the green key actually increased if half of the trials had 10-s green houselights followed by food and the other half had no green houselights followed by no food. The latter condition therefore demonstrated a case in which preference for an alternative increased when food was removed from half of the trials. The results suggest that the red and green houselights served as conditioned reinforcers. A hyperbolic decay model (Mazur, 1989) provided good predictions for all conditions by assuming that the strength of a conditioned reinforcer is inversely related to the total time spent in its presence before food is delivered.
55 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-778-348-905-085 tex.type: [object Object]
Keywords: Animal; Association Learning; Choice Behavior; Color Perception; Conditioning; Operant; Discrimination Learning; Mental Recall; Motivation; Pigeons; Reinforcement Schedule; Retention (Psychology); Support; U.S. Gov't; P.H.S.; animal; article; choice; color vision; conditioned reinforcement; decision making; delay of reinforcement; dept.psy; discrimination learning; instrumental conditioning; key peck; learning; long term memory; motivation; pigeon; pigeons; probability of reinforcement; recall; reinforcement